From the desk of Dr. Jack Chaplin. - Unknown:::Creator::::::::::::
Photo shows a hand written note stating: Taken: Oct 14, 1976 Machine shop with mini processor driving n/c machine built by Bogdan and students for Dr. Chaplin and Miller Photo by Burney." Printed at the top of the note is: From the desk of Dr. Jack Chaplin. Printed at the bottom of the note is: Industrial Studies Department.